VERBA TEMIRU: KAJIAN STRUKTUR - Aprilani, Felicia (Universitas Diponegoro, 2017)
The author analyzes the shape and function of the verb temiru and structure modification studies. The purpose of this study is to describe the shape and function of temiru verb in the sentence contained in the work of Banana Yoshimoto kitchin novel and novel Totto - chan Tetsuko Kuroyanagi work through the study of form and function. In this paper the author uses descriptive analysis method according to the theory Sudaryanto. According to research methods of descriptive analysis is done solely based on facts or phenomena that are empirically still used by native speakers so it can be described as is. For data analysis the authors use the method agih, namely the basic techniques Element For Direct ( BUL ). To analyze the data, the author uses the theory Yuriko Sunagawa et al. Based on this theory can be found in general function temiru verb meaning to try . <a href=